PERTUMBUHAN EKONOMI DAN PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT SUATU ANALISIS MODEL PERSAMAAN SIMULTAN - Hendarmin, Hendarmin (Fakultas Ekonomi dan Bisnis, UNTAN, 2011)
This study aims to obtain empirical evidence on (I) causality between economic growth and human development, (2) the influence of population, investment and human development to economc growth, (3) the influence of economic growth, expenditure government spending on education and health sector as well as on the human development in regency/city of West Kalimantan province. This study is characterized by descriptive as well as quantitative research, namely research that aims to giving picture or a characteristic of a particular phenomenon by using the model of simultaneous equations method of Two Stage Least Square (TSLS) approach to fixed effect model (FEM). The secondary data as used in the research such as panel data (the data aliance of time series and cross section) from 9 regency/city of West Kalimantan province during the period 2001- 2008. The research finding indicate that (I) there are two ways causality relationship between economic growth and human development, (2) population, investment, and human development have a significant influence and positively to economic growth, (3) economic growth, expenditure government spending on education and health sector has a positive and significant influence on the human development in regency/city West Kalimantan province. Key words : economic growth, human development, investment, government spending and two-way relationship, two stage least square/TSLS